Taxonomical identification, biomass production and nutrient composition of Moringa sp. as a fodder crop - Sharmin, F; Sarker, MSK; Sarker, NR; Huque, KS; Hossain, SMJ; Basher, MK (Bangladesh Journal of Livestock Research, 2020)
The study was conducted to identify the moringa species and to determine biomass production of Moringa sp. as a fodder crop. An experimental plot (2100 cm x 300 cm) was divided into three equal subplots (900 cm x 300 cm). Chemical fertilizer was applied (100-90-30, NPK), one-fifth of the total fertilizer after each harvest and the recommended amount of cow dung. Weeds were controlled in the experimental plot as they appeared. In a harvesting day, one unit of land containing 54 plants was cut into 3 different sections considering different cutting heights 1.5, 2 and 2.5 feet and cutting intervals after planting were 40, 50 and 60 days, respectively. The experimental design was 3 x 3 factorial design in this study. All plants were randomly selected from each harvested plot and separated manually into their different botanical fractions such as stem, twigs and leaves. The different fractions weight were recorded using an electric balance and freshly harvested biomass were sun dried. To identify the moringa plant taxonomically, the herbarium sheets were prepared with the samples from 6 different locations of Bangladesh. The herbarium sheets were matched with the control moringa herarium sheet at the library of Bangladesh National Herbarium Center, Mirpur Dhaka. As per result, the biomass yield of moringa at 40 days from sowing was significantly highest (p<0.01) in 1.5 feet (278 kg/hec) to 2 feet (264 kg/hec) cutting from the ground compared to 2.5 feet (207 kg/hec). Similar trends were observed in 60 days. Interaction effect between cutting height and cutting interval was found significant. Moringa leaves contained crude protein (CP) 28.21% whereas stem and twigs contained 11.13% and 13.49% CP respectively in this study. Considering all the results it can be concluded that M. olifera may be cultivated as fodder crop and harvested with optimum cutting height of 1.5 feet at the age of 60 days. Bang. J. Livs. Res. Vol. 26 (1&2), 2019: P. 61-72